2017
DOI: 10.3791/55268
|View full text |Cite
|
Sign up to set email alerts
|

<em>In Vitro</em> Differentiation of Human Pluripotent Stem Cells into Trophoblastic Cells

Abstract: SHORT ABSTRACT We present a protocol to efficiently generate human trophoblastic cells from human pluripotent stem cells using bone morphogenic protein 4 and inhibitors of the Activin/Nodal pathways. This method is suitable for efficient differentiation of human pluripotent stem cells, and can generate large quantities of cells for genetic manipulation. LONG ABSTRACT The placenta is the first organ to develop during embryogenesis, and is required for survival of the developing embryo. The placenta is compris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…Complete differentiation of hESCs into trophoblast-like cells (EVTs, SYNs) requires 9-14 days [9]; here, we limited differentiation to days 2-5 to investigate sex-specific differences with the early commitment for differentiation into trophoblastic cells. We observed morphological changes after 1 day of BMP4/A/P differentiation, with cells appearing flatter and larger with enlarged nuclei, as previously observed [6,51]. Cellular differentiation was confirmed using quantitative PCR for the pluripotency marker NANOG, which decreased by day 2, and expression of trophectoderm markers KRT7 and CDX2, whose expression peaked at days 2-4 (data not shown), as described previously [9,51].…”
Section: Male and Female Hescs Exhibit Similar Efficiency For In Vitrsupporting
confidence: 87%
See 1 more Smart Citation
“…Complete differentiation of hESCs into trophoblast-like cells (EVTs, SYNs) requires 9-14 days [9]; here, we limited differentiation to days 2-5 to investigate sex-specific differences with the early commitment for differentiation into trophoblastic cells. We observed morphological changes after 1 day of BMP4/A/P differentiation, with cells appearing flatter and larger with enlarged nuclei, as previously observed [6,51]. Cellular differentiation was confirmed using quantitative PCR for the pluripotency marker NANOG, which decreased by day 2, and expression of trophectoderm markers KRT7 and CDX2, whose expression peaked at days 2-4 (data not shown), as described previously [9,51].…”
Section: Male and Female Hescs Exhibit Similar Efficiency For In Vitrsupporting
confidence: 87%
“…We observed morphological changes after 1 day of BMP4/A/P differentiation, with cells appearing flatter and larger with enlarged nuclei, as previously observed [6,51]. Cellular differentiation was confirmed using quantitative PCR for the pluripotency marker NANOG, which decreased by day 2, and expression of trophectoderm markers KRT7 and CDX2, whose expression peaked at days 2-4 (data not shown), as described previously [9,51]. We verified that CDX2 and KRT7 proteins were expressed during BMP4/A/P differentiation using IF, and these markers appeared between days 2 and 3 of differentiation (Fig.…”
Section: Male and Female Hescs Exhibit Similar Efficiency For In Vitrsupporting
confidence: 86%
“…Within this context, some authors found that medium conditioned by factors such as activin A, bone morphogenetic protein 4 (BMP4), vascular endothelial growth factor (VEGF) or Dickkopf-related protein 1, can optimize cardiac development in mouse and human stem cell lines[46,47]. BMP4 itself, in combination with inhibitors of the Activin/Nodal signaling pathways, induces differentiation of ESCs into trophoblastic cells, which show similar trophectoderm profile and are able to secrete placental hormones[48]. Concerning the use of chemistry to push stem cells to specific phenotypes, molecules that can affect the epigenetic code to activate a molecular differentiation program have largely been used.…”
Section: In Vitro Modulation Of Stem Cell Behaviormentioning
confidence: 99%
“…With the use of BMP4 and the 2 inhibitors A83-01, PD173074 (BAP), the derived trophoblast-like cells express trophoblastic markers ( KRT7 , HLA-G , CGB ), secrete hormones (β-hCG, estrogen, and progesterone) and possess invasive ability [82,85] . The BAP-induced trophoblast from hESCs was reported to be a suitable model system for studying early human placentation [86] .…”
Section: Stem Cell-based Models Of Embryo Surrogates For Implantation...mentioning
confidence: 99%